Plant microtechnique and microscopy - Ruzin, Steven E. (New York, Oxford University Press, 1999)
Plant Microtechnique and Microscopy surpases all previously written manuals by providing an in-depth coverage of the field of microtechnique. The traditional paraffin method is covered in explicit step-by-step protocols, with theoretical background included to give students the tools required to design their own experiments and interpret existing results. In addition, the theory and practice of modern applications, such as methacrylate embedding and sectioning, microwave tissue processing, flourescence histochemistry, and in situ hybridization, are documented thoroughly. Preceding Chapter One are ten single-page "Quick Start" protocols. Patterned after computer software manuals, these abbreviated instructions provide the experienced student with the fundamental steps to complete the ten microtechnique protocols most frequently used today. Appendices on laboratory practice (chemical toxicites, common calculations, and buffer tables) are provided to make this volume a valuable addition to every biological laboratory. Plant Microtechnique and Microscopy contains a definitive chapter on microscopy and, with diagrams and text, describes the optical principles of techniques such as phase contrast, DIC, confocal and deconvolution wide-field microscopy. Also included is an extensive appendix on optics and its application to the microscope. The book's bibliography of over 650 references is a substantial resource for any student of histology, histological technique, or microscopy.
Bibliography 289-306p; Index 307-322p; ^n23/CSL/IEB/2002-2003/237^d2003-03-17^mPurchase
Keywords: Microscopy; Botany